Diagnostic Accuracy of Fingerstick β‐Hydroxybutyrate for Ketonuria in Pregnant Women With Nausea and Vomiting. (27th August 2013) - Ferguson, Ian; Mullins, Michael E.
Abstract: Objectives: The aim of this study was to determine whether a rapid, fingerstick β‐hydroxybutyrate (β‐OHB) test predicts ketonuria in pregnant women with nausea and vomiting. Methods: A convenience sample of 82 pregnant women who presented to the Barnes‐Jewish Hospital emergency department (ED) with complaints of nausea or vomiting were enrolled into an institutional review board–approved, prospective, observational study. Exclusion criteria were temperature of >38.3°C, altered mental status, prisoners, and >1 L of any intravenous (IV) fluid before screening. Subjects had fingerstick β‐OHB tests, with results reported in increments of 0.1 mmol/L. Urine ketone results were made available once reported as part of standard care and varied from 0 (trace) to +4 values. Ketonuria was defined as a urine ketone value of 3+  or 4+  and was analyzed as a dichotomous, categorical variable. A contingency table and receiver operator characteristic (ROC) curve were constructed for comparing the β‐OHB values to those urine ketone values for each patient. Results: Mean (±SD) β‐OHB was 0.43 (±0.52) mmol/L, and median urine was 1+  for the cohort as a whole. The area under the ROC curve equaled 0.95. The sensitivity and specificity for a fingerstick test of >0.45 mmol/L were 89 and 94.5%, respectively. The positive likelihood ratio (LR) was 16, and the negative LR was 0.12. Conclusions: Fingerstick β‐OHB is a rapid and reliable diagnostic tool that correlates well with ketonuria and identifies ketonemia in pregnant women with nausea and vomiting. Fingerstick β‐OHB testing has the potential to increase triage efficiency, shorten length‐of‐stay times, and positively affect patient outcomes in an ED setting.